2020
DOI: 10.1136/annrheumdis-2020-218189
|View full text |Cite|
|
Sign up to set email alerts
|

Parsing multiomics landscape of activated synovial fibroblasts highlights drug targets linked to genetic risk of rheumatoid arthritis

Abstract: ObjectivesSynovial fibroblasts (SFs) are one of the major components of the inflamed synovium in rheumatoid arthritis (RA). We aimed to gain insight into the pathogenic mechanisms of SFs through elucidating the genetic contribution to molecular regulatory networks under inflammatory condition.MethodsSFs from RA and osteoarthritis (OA) patients (n=30 each) were stimulated with eight different cytokines (interferon (IFN)-α, IFN-γ, tumour necrosis factor-α, interleukin (IL)-1β, IL-6/sIL-6R, IL-17, transforming gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 50 publications
1
31
1
Order By: Relevance
“…This may be because the abnormal proliferation of FLSs in RA requires a large amount of nutrients, and the high concentration of L-arginine promotes the proliferation of FLSs and the activation of immune cells: the amount of cytokines secreted by the increased FLSs increases, and the activation of immune cells also secretes many cytokines. Furthermore, previous studies have shown that in addition to IL-1β, IL-6, and IL-8, other cytokines, such as TNF-α and IFN-γ, are also elevated in RA articular uid [22][23][24][25], but in this study, there was no signi cant difference compared to the concentrations observed in OA synovial uid. This may be due to the small sample size (only 9 samples were used in this study), or perhaps different control samples should have been selected.…”
Section: Discussioncontrasting
confidence: 86%
“…This may be because the abnormal proliferation of FLSs in RA requires a large amount of nutrients, and the high concentration of L-arginine promotes the proliferation of FLSs and the activation of immune cells: the amount of cytokines secreted by the increased FLSs increases, and the activation of immune cells also secretes many cytokines. Furthermore, previous studies have shown that in addition to IL-1β, IL-6, and IL-8, other cytokines, such as TNF-α and IFN-γ, are also elevated in RA articular uid [22][23][24][25], but in this study, there was no signi cant difference compared to the concentrations observed in OA synovial uid. This may be due to the small sample size (only 9 samples were used in this study), or perhaps different control samples should have been selected.…”
Section: Discussioncontrasting
confidence: 86%
“…Under microscope, RA was characterized by synovial inflammation and hyperplasia with pannus formation, causing bone and cartilage destruction [ 46 ]. In synovial tissues, lymphocytes and synoviocytes produced excessive inflammatory cytokines, such as IL-6, IL-1β and TNF-α, leading to synovitis [ 47 ]. Furthermore, cytokine stimulated synoviocytes secreted MMP and receptor activator of nuclear factor kappa B ligand (RANKL) into SF and consequently lead to cartilage degradation and joint destruction [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…APTO-253 was administered at 25 mg/kg i.p. (a dose based on that employed in a mouse model of arthritis 30 ) every other day beginning at day 9 post-bleomycin until day 19, and lungs were harvested on day 21 (Figure 6A). As previously shown with this same model in Figure 4, bleomycin administration resulted in severe alveolar obliteration (Figure 6B and Supplemental Figure 12) and a significant increase in lung hydroxyproline content (Figure 6C).…”
Section: Therapeutic Administration Of Apto-253 Protects Mice From Bl...mentioning
confidence: 99%